Aharonov–Bohm effect for a fermion field in a planar black hole “spacetime” - M. A. Anacleto; F. A. Brito; A. Mohammadi; E. Passos (European Physical Journal C: Particles and Fields, 2017)
Abstract In this paper we consider the dynamics of a massive spinor field in the background of the acoustic black hole spacetime. Although this effective metric is acoustic and describes the propagation of sound waves, it can be considered as a toy model for the gravitational black hole. In this manner, we study the properties of the dynamics of the fermion field in this “gravitational” rotating black hole as well as the vortex background. We compute the differential cross section through the use of the partial wave approach and show that an effect similar to the gravitational Aharonov–Bohm effect occurs for the massive fermion field moving in this effective metric. We discuss the limiting cases and compare the results with the massless scalar field case.